The chickens and pigs of the Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Monogastric Livestock Industry in the South Pacific Region. Status, Production Systems and Constraints By A O Ajuyah & M Umar. Institute of Research, Extension and Training in Agriculture (IRETA), 2001. 48 pp. ISBN 982 175 157 1 US$ 20 Euro 22.3